Analytische Lösungen einer Klasse linearen Gleichungen mit partiellen Ableitungen - Kisielius, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. В. Киселюс. Аналитические решения одного класса линейных уравнений в частных производных J. Kisielius. Vienos tiesinių lygčių su dalinėmis išvestinėmis klasės analiziniai sprendiniai